The orthopedic patient and limb amputation: impact of traditional beliefs on acceptance in Port Harcourt, Nigeria - Aaron, Friday E.; Ijah, Rex Friday Ogoronte A.; Obene, Tonye (International Surgery Journal, 2021)
Background: Aim of the study was to ascertain the awareness on surgical limb amputation and establish the existence of traditional beliefs that impacts on acceptance of surgical limb amputation in tertiary healthcare facilities in Port Harcourt. Surgical limb amputation is a form of treatment recommended in conditions of dead, dying, dangerous limb or damn nuisance, in which the appendage is removed surgically and permanently from the rest of the body. Methods: A cross-sectional descriptive study was carried out among patients and patients’ relatives in the two government-owned tertiary health care facilities that offered orthopedic surgical services in Port Harcourt using self-administered questionnaires. Data obtained was analyzed using the Statistical Package for the Social Sciences (SPSS) version 20.0. Results: Safe removal of a disease limb from the rest of the body was considered by 217 respondents (93.1%) as the meaning of limb amputation. Some community beliefs on amputated limb were: risk of incomplete body in the “next world”, burying of persons with amputated limb in the evil forest when they die, stigmatization as outcasts in some communities. Eighty-two respondents (35.2%) opined that traditional bone setters should be encouraged to continue their work. Conclusions: There was high awareness on limb amputation among respondents. Though expressed by few respondents, the twin factors of patronage of traditional bone setters and the practice of community stigmatization of amputees / social isolation among others explains patients decline of offer of limb amputation in the care of orthopedic patients in our society.